Novel multiplex PCR approach for the detection of Erysipelothrix rhusiopathiae, Streptococcus suis, and Staphylococcus hyicus in swine - Milton, A. Arun Prince; Khan, Sabia; Srinivas, Kandhan; Basar, Torik; Hussain, Zakir; Priya, G. Bhuvana; Saminathan, M.; Puii, L. H.; Ghatak, Sandeep; Das, Samir (Frontiers in Veterinary Science, 2025)
Erysipelothrix rhusiopathiae, Streptococcus suis, and Staphylococcus hyicus are neglected, emerging and zoonotic pathogens in pigs that share common clinical signs and lesions, particularly septicaemia and skin lesions, highlighting the need for differential diagnosis. Currently, no single diagnostic assay is available to test samples for confirmation of the presence of all three pathogens. To address this, a novel multiplex PCR-based detection assay was optimized and evaluated for the simultaneous detection of E. rhusiopathiae, S. suis, and S. hyicus targeting the, 23S rRNA, recN, and sodA genes, respectively. The optimized multiplex PCR demonstrated 100% analytical specificity, with a detection limit of 104 copies/μL for E. rhusiopathiae and S. hyicus, and 106 copies/μL for S. suis. The assay was further validated by comparison with previously established uniplex PCR assays and tested on field-collected pig blood samples to assess real-world applicability. The developed assay is rapid, specific and cost-effective and can serve as a handy diagnostic tool for testing suspect samples for these neglected bacterial pathogens of pigs.